Study of Roman architecture plans through the archaeological evidence of the city of Tipasa - Algeria - Dahmani, Malika; Salim Guebboub, Lakhdar (Journal of Architecture and environment of child, 2023)
of Tipaza was known for the construction of many residential buildings, public buildings and open spaces during the Roman period, according to a planning system followed by the Roman engineer, the most important of which are: temples, the theater and the forum, which provide some models for the plans of Roman urban facilities, as it added systems to the world heritage Schematically not known before. And the Romans are considered one of the greatest empires of antiquity that built great types of facilities and urbanization. This research aims to give an image of the Roman planning system through a descriptive study and analysis of the archaeological evidence of the city of Tipasa.